Heat-treatment effects on dimensional stability and mechanical properties of 3D printed continuous carbon fiber-reinforced composites. (August 2021) - Wang, Kui; Long, Hongmei; Chen, Ying; Baniassadi, Majid; Rao, Yanni; Peng, Yong
Abstract: This paper investigated the heat-treatment effects on the performances of 3D printed continuous carbon fiber (CCF) reinforced composites (CCFRCs). Specimens with different layer distributions were post-treated at different heat-treatment conditions. The heat-treatment influences on material's crystallinity, porosity and dimensional stabilities with underlying mechanisms were discussed. Flexural properties of the composites were also evaluated by linking the structure evolution and deformation mechanism with heat-treatment. The result showed that the dimensional change of CCFRCs during heat-treatment was much closely related to the microstructure change than the material crystallization. Besides, heat-treatment could improve the mechanical properties of CCFRCs by decreasing porosity accompanied with interface strengthening. Namely, heat-treatment helpfully delayed the crack initiation of CCFRCs during bending tests through the change of failure mode of matrix layers and the improved bonding between fiber-bundles/matrix.